A recepção do epos vergiliano na poesia épica de Basílio da Gama : da neolatina Brasilienses Aurifodinae à vernácula O Uraguay - Nascimento, Dreykon Fernandes (2024)
The present thesis aims at analyzing the reception of Vergil’s epos, composed by the corpora of the Bucolics, the Georgics and the Aeneid, into two epic poems written by the Luso-Brazilian poet Basílio da Gama: into the Brasilienses Aurifodinae or Brazilian goldmines, a didactic epic poem, circulated only in manuscript form, and composed entirely in Latin in some point between 1760-1762; and also into O Uraguay, a heroic epic poem, produced in the vernacular Portuguese and printed in 1769. Thus, our study seeks particularly setting up a conception of epic genre divided in three types or species, and summarized by Vergil’s poems: a lyric species based on the Bucolics; a didactic one based on the Georgics; and a heroic one based on the Aeneid. Therefore, reliant on this triadic structure, we argue that both Brasilienses Aurifodinae and O Uraguay, respectively, fit in the didactic and heroic epic species, imitating and emulating rhetorical places of invention, disposition and elocution foreseen by the Vergilian epos, which means that our study stands against the romantic criticism that supposes Basílio da Gama would be actually in contravention of classical rules predicted to all oral and written text until the 18th century. Therefore, to achieve our purpose, we reconstructed verisimilar coding and decoding systems, based on poetic and rhetorical arts from Greco-Latin Antiquity, updated politically-theologically over the 16th, 17th and 18th century, in order to circumvent certain avoidable anachronisms by undertaking a sort of homology of first legibility proper for those texts which we work with